Ivabradine improves survival and attenuates cardiac remodeling in isoproterenol‐induced myocardial injury. (7th November 2020) - Simko, Fedor; Baka, Tomas; Repova, Kristina; Aziriova, Silvia; Krajcirovicova, Kristina; Paulis, Ludovit; Adamcova, Michaela
Abstract: This study investigated whether ivabradine, a selective If current inhibitor reducing heart rate (HR), is able to improve survival and prevent left ventricular (LV) remodeling in isoproterenol‐induced heart damage. Wistar rats were treated for 6 weeks: controls ( n = 10), ivabradine (10 mg/kg/day orally; n = 10), isoproterenol (5 mg/kg/day intraperitoneally; n = 40), and isoproterenol plus ivabradine ( n = 40). Isoproterenol increased mortality, induced hypertrophy of both ventricles and LV fibrotic rebuilding, and reduced systolic blood pressure (SBP). Ivabradine significantly increased survival rate (by 120%) and prolonged average survival time (by 20%). Furthermore, ivabradine reduced LV weight and hydroxyproline content in soluble and insoluble collagen fraction, reduced HR and attenuated SBP decline. We conclude that ivabradine improved survival in isoproterenol‐damaged hearts.